Relasi Teologi Aswaja Dengan Ham Perspektif Kiai Said Aqil Siroj - Budi Harianto (Institut Ilmu Keislaman Zainul Hasan Genggong, 2018)
Abstract: The definition of Ahl al-Sunnah Wa al-Jama'ah resulted from the construction of Kiai Said Aqil Siroj's thought ie Ahl al-Sunnah Wa al-Jama'ah as manhaj al-fikr al-din al-syamil 'ala syu'un al-hayat wa muqtadhayatiha al-qaim 'ala asas al-tawassuth wa al-tawazun wa al i'tidad wa al-tasamuh (a method of religious thought that encompasses all aspects of life and stands on the principle of equilibrium in aqidah, mediator and adhesive in social life, and justice and tolerance in politics). Kyai Said Aqil Siroj's typology of thought is an inclusive (open) religious typology and the Ahl al-Sunnah Wa al-Jama'ah perspective of Kiai Said can be said of the inclusiveness of Ahl al-Sunnah Wa al-Jama'ah. So Ahl al-Sunnah Wa al-Jama'ah must contain tawasut, tasamuh, tawazun and i'tidal in acting or thinking. So as to respond to new things in modern life such as human rights. Keywords: HAM, Ahl as-Sunnah Wa-al Jama'ah, Justice, Freedom, Equality.